2014
DOI: 10.1155/2014/236905
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: Sex-Dependent Variations in Presentation and Management

Abstract: Sarcoidosis is an inflammatory disease with a wide range of clinical presentations. The manifestations and prognosis in sarcoidosis are dependent upon not only organ involvement but also age and sex. The purpose of this review is to describe the systemic and ocular manifestations of sarcoidosis with a specific focus on sex-dependent difference in presentation and management. Sarcoidosis is more common in women, particularly in patients who present after age of 50 years. Women with sarcoidosis are more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 57 publications
2
34
1
Order By: Relevance
“…Gender is important for many epidemiological and clinical characteristics, including sarcoidosis treatment options and prognosis [2]. Many autoimmune diseases are more common in females, and sarcoidosis is no exception [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gender is important for many epidemiological and clinical characteristics, including sarcoidosis treatment options and prognosis [2]. Many autoimmune diseases are more common in females, and sarcoidosis is no exception [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although ACE is not specific for sarcoidosis, it is used as a diagnostic and prognostic marker because its serum concentration is high in 60%-70% of patients depending on disease extent and activity [2,17]. Although some researchers report that there is no difference regarding ACE activities between sexes [2,18], one Turkish study reported there were more females and serum ACE levels were significantly lower among patients over 50 years of age with sarcoidosis [3]. We found a significant decrease in serum ACE values among patients ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus hormonal therapy may be considered as a possible therapeutic adjunct for sarcoidosis patients. 162, 163 …”
Section: Discussionmentioning
confidence: 99%